2022
DOI: 10.3390/en15165950
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Demand Forecasting with Use of Artificial Intelligence: The Case of Gokceada Island

Abstract: This study reviews a selection of approaches that have used Artificial Neural Networks (ANN), Particle Swarm Optimization (PSO), and Multi Linear Regression (MLR) to forecast electricity demand for Gokceada Island. Artificial Neural Networks, Particle Swarm Optimization, and Linear Regression methods are frequently used in the literature. Imports, exports, car numbers, and tourist-passenger numbers are used as based on input values from 2014 to 2020 for Gokceada Island, and the electricity energy demands up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The MLR model is a methodology that establishes the causal relationship between independent and dependent variables through a mathematical framework. The MLR model accurately defines the connections among these variables, precisely characterising their associations [3].…”
Section: Multiple Linear Regression Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLR model is a methodology that establishes the causal relationship between independent and dependent variables through a mathematical framework. The MLR model accurately defines the connections among these variables, precisely characterising their associations [3].…”
Section: Multiple Linear Regression Modellingmentioning
confidence: 99%
“…Electricity load forecasting aims to achieve a harmonious balance between production and consumption, utilizing the potential of forecasting models [2,3]. Precise electricity load forecasting can mitigate the risk of power outages and reduce the expenses associated with surplus electricity generation capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in terms of comparing the suitability of the artificial intelligence models, the evidence in the literature is mixed as to the most optimum machine learning algorithm to model electricity demand. For instance, Abdusalam et al (2016), Melodi et al (2017), Saglam et al (2022), andHasanah et al (2020) provided evidence that supports the optimal performance of neural network ML algorithm; however, Chapagain et al (2020), Yotto et al (2023 and Eya et al (2023) refuted their optimal performance. However, studies about electricity demand modelling using ML techniques for Nigeria, such as Abdusalam et al (2016), Melodi et al (2017) and Adewuyi et al (2020) adopted the neural network algorithms, but Eya et al (2023) that also used the neural network algorithms for Nigeria reported that the algorithm underperformed compared to artificial neuro-fuzzy inference system (ANFIS) algorithm.…”
Section: Table 23 Herementioning
confidence: 99%
“…The authors in [ 10 ] investigate electricity demand forecasting using artificial intelligence techniques, focusing on Gokceada Island as a case study. While this study does not directly address electricity theft, it underscores the importance of accurate forecasting methods in managing energy resources effectively.…”
Section: Introductionmentioning
confidence: 99%